Upah Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan - Ayung Wijia Lestari; Siti Ning Farida (IPM2KPE, 2022)
This study aims to determine the influence of wages and work environment on employee performance at CV Andi Jaya Mojokerto. This research method is descriptive quantitative. The population used is all employees of CV Andi Jaya. The sampling technique used is saturated sampling technique, which takes the entire sample of 45 people. Data analysis was performed using multiple linear regression analysis. The results showed, a) the significance value of the wage variable (X1) was 0.302 > 0.05, and the t value was 1.045 <2.018; b) the significance value of the Work Environment variable (X2) is 0.000 <0.05 and the tcount is 4,242 > 2,018; c) F Count > F Table or 15,413 > 3.22 and a significance value of 0.000 <0.05. In conclusion, partially wages (X1) have no positive and significant effect on employee performance. Work environment (X2) partially has a positive and significant effect on employee performance. And simultaneously or simultaneously wages and work environment have a positive and significant effect on employee performance (Y) CV Andi Jaya Mojokerto. Keywords: Employee Performance, Work Environment, Wages